KUALITAS PELAYANAN KESEHATAN DI PUSAT KESEHATAN MASYARAKAT KEMBANG SERI KECAMATAN TALANG EMPAT KABUPATEN BENGKULU TENGAH - Yoki Apriyanti; Evi Lorita; Yusuarsono Yusuarsono (Professional: Jurnal Komunikasi dan Administrasi Publik, 2019)
his study aims to find out the quality of health services in Kembang Seri Public Health Center atTalang Empat Sub-District, Central Bengkulu Regency. This research is a qualitative research presented descriptively. The informants in this study amounted to 6 people consisting of key informants and principal informants. The data were collected by interviews, observation and documentation method. The technique data analysis used were data reduction, data presentation, and conclusion. Based on the results show that the quality of Health Services in the Kembang Seri of Talang Empat Sub-District of Central Bengkulu Regency is seen from the theory of service quality 1)The Reliability has done a good service but nurses are still not friendly in patient. 2) Responsiveness of nurses are ready and sufficiently skilled in treating patients but there are also nurses who are still arrogant and play their own cellphones while patients need service.3) Assurance of nurses are less friendly and polite to patients and nurses still distinguish services from rich patients and poor patients in terms of service but nurses are active in communicating with patients. Empathy of nurse is easily contacted in every room that keeps and communicates with the patient ready to be called by the patient’s family if needed. However, in terms of medicines and intravenous needles there is still a lack of availability. 5. Tangibles (Physical Facilities) seen from the building of Kembang Seri Public Health Center is good and medical equipment is sufficient.